A useful measeurement of serum pepsinogen and urinary anti-Helicobacter pylori antibody in human dry doch: comparative urinary anti Hp assay (ELISA) and serum anti Hp titration (HM-CAP method) - ARAKAWA, Yasuyuki; KAWAMURA, Yo; ONO, Yosiki; OHTANI, Takesi; HIRAI, Takasi; IWASAKI, Ariyosi; OGIWARA, Akifumi; KURIHARA, Ryuiti; UEHARA, Takesi (Journal of Gastroenterological Mass Survey, 2003)
Third Department of Internal Medicine Nihon University School of Medicine We studied the utility of and problems associated with stomach cancer testing by pepsnogen (PG) method and anti Helicobacter pylori (Hp) assay simultaneously, on 1, 011 subjects (mean age: 50±9.55years; male: 701; females: 310) examined at the General Examination Center at Nihon University School of Medicine form January 10 to August 31, 2001. Anti Hp assay was peformed by urinary anti Hp assay (chromatography). ELISA also revealed a correlation between urinary anti Hp assay and serum anti Hp titration (HM-CAP method). This was thus a useful test method for health screening. Although there were two cases of stomach cancer detected among positive cases by both PG method and anti Hp antibody, there were no cases of stomach cancer seen among the 517 negative cases to both PG method and urinary anti Hp antibody. In the testing of stomach cancer. Age and locality need to be studied for setting a stomach cancer high-risk group by PG method and anti Hp assay simultaneously, but it is possible to set a stomach cancer low-risk group.